STUDY OF HEAVY METAL CONTENT IN BOTTOM SEDIMENTS AND WATER IN THE DIVERSION CHANNEL OF RICE IRRIGATION SYSTEM - Tatyana I. Drovovozova; Lyubov A. Bulgakova; Mikhail V. Vlasov; Natalia N. Krasovskaya (Мелиорация и гидротехника)
Purpose: to conduct hydrochemical studies of water and bottom sediments, as well as to assess their hazard level in the diversion channel of the rice irrigation system. The relevance of the research is due to the entry of a large number of pollutants into water bodies, especially from rice irrigation systems. Materials and methods. The assessment of the pollution level of bottom sediments with heavy metals was carried out by indices: pollution factor and degree, geoaccumulation index; aquatic environment – by the anthropogenic load index, mixture toxicity index. The materials for assessing the pollution level of water and bottom sediments were the results of field observations of the collector, through which drainage waters from the rice irrigation system are diverted to the Don River. Results. The content of such heavy metals as iron, manganese, copper, lead and zinc was studied in the collector-drainage runoff and bottom sediments. The content of exchangeable manganese and total forms of copper and zinc in the bottom sediments of the collector exceeds the background concentrations in the bottom sediments of the Don River by 1.2–4.9 times. The ecological state of the bottom sediments of the collector is characterized as moderately polluted. The content of manganese in the collector-drainage water exceeds the maximum permissible concentrations by 154–223 times, iron by 4–5 times, copper by 5 times. The assessment of the quality of bottom sediments in terms of soil pollution with heavy metals showed a weak nature of their pollution. Conclusions. The high content of manganese, copper and iron characterizes the bottom sediments as a source of secondary pollution of collector-drainage waters in the collector, however, compared with the maximum permissible concentrations of heavy metals for soils, their content is not exceeded. The establishment of environmental safety and the development of methods for the bottom sediments disposal require further research.